The Potential Role of Marine Protein Hydrolyzates in Elevating Nutritive Values of Diets for Largemouth Bass, Micropterus salmoides - Dai, Min; Li, Songlin; Fu, Cefeng; Qiu, Hongjie; Chen, Naisong (Frontiers in Marine Science, 2020)
The study was conducted to explore the improvement function of marine protein hydrolyzates on nutritive values of diets for largemouth bass. The diet with no inclusion of marine protein hydrolyzate was considered as the control (NC), and four other diets were formulated with fish soluble (FS), squid paste (SqP), shrimp paste (ShP), or a mixture of FS, SqP, and ShP (Mix). Triplicate tanks of fish were fed to apparent satiation twice daily for 81 days. Results showed that the growth performance was elevated due to the inclusion of marine protein hydrolyzates along with significantly elevated feed intake and protein digestibility. Thereinto, the inclusion of FS and ShP significantly improved the growth performance compared to NC. The supplementation of marine protein hydrolyzates elevated the protein content and lysozyme activity of serum, but significantly decreased the activity of liver alanine transaminase and aspartate transaminase. The gene expression analysis revealed that marine protein hydrolyzate inclusion up-regulated the expression of insulin-like growth factor I (IGF-I) with increased expression of TOR pathway-related genes including protein kinase B (AKT) 1 and ribosomal protein S6. However, the expression of activating transcription factor 4 (ATF4) and regulated in development and DNA damage responses 1 (REDD1) involved in the amino acids response (AAR) pathway was depressed with the addition of marine protein hydrolyzates. The activation of the TOR pathway and depression of the AAR pathway may be beneficial for the improved performance of fish. In the above, the marine protein hydrolyzate, especially FS and ShP, can elevate nutritive values of diets for largemouth bass.